Error analysis on students’ essay writing: A case study - Surjowati, Ribut (Englisia: Journal of Language, Education, and Humanities, 2023)
The objective of this research is to determine the types of errors committed by the students of the English Department at the Faculty of Language and Science, Wijaya Kusuma Surabaya University (FBS UWKS), as well as to describe the origins of these errors. The research conducted was descriptive in nature, utilizing qualitative methods. The participants involved in the study were fourth semester students of the English Department at FBS UWKS. Out of the 20 participants, a total of 80 data sources were obtained during the learning process. The researchers collected the data through the use of interview sheets and essays. Once collected, the data underwent a process of reduction, classification, display, and analysis. The procedures for data analysis were outlined as follows: 1) the collection of essays, 2) the classification, counting, and analysis of errors based on the error types proposed by Brown (2007), and 3) the analysis of errors to identify their sources using the concepts of interlingual transfer and intralingual transfer as proposed by Brown (2007) and Touchie (1986). From the analysis, it was discovered that the errors could be categorized into two main groups, namely essay organization errors and grammatical errors. The essay organization errors consisted of seven classifications, including issues with the thesis statement, topic sentences, unity, coherence and cohesion, as well as supporting sentences. On the other hand, the grammatical errors encompassed omission, addition, and punctuation mistakes. The sources of these errors were found to be inadequate learning, false conceptualizations, overgeneralization, and ineffective teaching practices.